MIE BASAH SUBSTITUSI TEPUNG RUMPUT LAUT (EUCHEUMA COTTONII) DAN TEPUNG KACANG MERAH (PHASEOULUS VULGARIS L) SEBAGAI ALTERNATIF MAKANAN TINGGI SERAT DAN ISOFLAVON - Mangkawa, Seprini Annavony; Purnawan, Asep Iwan; Fitria, Mona; Surmita, Surmita; Agung, Fred; Mulyo, Gurid PE (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Cardiovascular disease is part of heart and blood vessel disorders including stroke, rheumatic heart disease and other conditions. One of the risk factors that increase the incidence of cardiovascular disease is hypercholesterolemia. Based on data from the 2013 Basic Health Research in Indonesia, the prevalence of hypercholesterolemia in the population aged more than 15 years is 35.9% and is a combination of the population in the borderline high category (total cholesterol value 200-239 mgdL) and high (total cholesterol value >240 mgdL). This study aims to determine the effect of the formulation between seaweed flour and red bean flour on the quality of wet noodles which include aspects of acceptability and nutritional quality including organoleptic properties, fiber content, and isoflavone content. The design used is an experimental study with the research method used is hedonic test for testing organoleptic properties, enzymatic method for testing food fiber content and HPLC method for testing isoflavone levels. The formula of seaweed flour and red bean flour consists of 3 balances, namely F1 (70%:30%), F2 (60%:40%), F3 (50%:50%). From the results of the study, it can be concluded that there are no significant differences in aspects of color and aroma, but there are significant differences in aspects of taste and texture. As for the results of testing the fiber content of wet noodles substituted with seaweed flour and red bean flour, the balance of 70%:30% is 11.7 grams, the balance is 60%:40% is 14.4 grams and the balance is 50%:50% is 13.5 grams. The results of testing the levels of isoflavones in wet noodles substituted with seaweed flour and red bean flour balance 70%:30% 10.2 mg, 60%:40% balance 15.5 mg and 50%:50% balance 26.6 mg.